HUBUNGAN STATUS GIZI DAN FAKTOR RISIKO LAINNYA TERHADAP KEJADIAN TB PARU - Pakpahan, Citra Prastika; Winda Septiani; Christine Vita Gloria Purba; Agus Alamsyah; Yuyun Priwahyuni (IKES Payung Negeri Pekanbaru, 2025)
Tuberculosis is an infectious disease caused by Mycobacterium tuberculosis that can attack the lungs and other organs. The purpose of this study was to determine the risk factors of nutritional status, knowledge, occupation, and smoking habits on the incidence of tuberculosis. This study used a quantitative observational method with a case-control design. The study was conducted in the Sidomulyo Community Health Center working area in Pekanbaru City. A total of 124 respondents participated in this study, consisting of 62 respondents with pulmonary tuberculosis and 62 control respondents without pulmonary tuberculosis, selected using simple random sampling techniques. Data collection used questionnaires and cross analysis, which consisted of univariate analysis and bivariate analysis with the Chi-square test to examine the relationship between independent and dependent variables. The results showed that there was a significant relationship between nutritional status and the incidence of pulmonary tuberculosis (P=0.030) OR 2.371 (1.147-4.899), knowledge (P= 0.031) OR 2.348 (1.142-4.829), occupation (P=0.028) OR 2.059 (1.004-4.222) and smoking habits (P=0.012) OR 2.703 (1.304-5.603). From the results of the study, it can be concluded that nutritional status, knowledge, occupation, and smoking habits are risk factors for pulmonary tuberculosis in the working area of the Sidomulyo Community Health Center in Pekanbaru.